Thermal buckling of oil-filled fixed-roof tanks subjected to heat radiation by a burning tank. (August 2022) - Li, Yunhao; Jiang, Juncheng; Yu, Yuan; Wang, Zhirong; Xing, Zhixiang; Zhang, Qingwu
Highlights: Thermal buckling behavior and fire resistance of oil-filled steel tanks. The effects of the height-to-diameter ratio, fluid level, and wall thickness. The oil-filled tank has a similar thermal buckling mode to the empty tank. Abstract: The thermal buckling behaviors of oil-filled tanks subjected to heat radiation of a burning tank are investigated considering the effect of isopentane on the heat transfer. The effects of the height-to-diameter ratio, fluid level, and wall thickness on the thermal buckling behavior and fire resistance of oil-filled tanks are studied, and the failure mechanism of the steel tank is analyzed based on the temperature and stress distributions. The results indicate that the buckling area is located at the upper part of the tank which is exposed to air. The oil-filled tank has a similar thermal buckling mode to the empty tank. Moreover, the height-to-diameter ratio, fluid level, and wall thickness hardly affect the thermal buckling mode of the oil-filled tank. This study can be used to optimize the design of steel oil tanks to resist fire accidents and lessen the loss triggered by fire accidents in tank farms.